Aerobic Endurance (VO2Max) Male Volleyball Student Activity Unit Doktor Nugroho University Magetan - R. Hariyo Padmoyo; Ridha Kurniasih Astuti (Journal of Physical Education Health and Sport, 2024)
The background of this research is that there is no measurement of aerobic endurance (VO2Max) for participants in the Men’s Volleyball Student Activity Unit Doktor Nugroho University Magetan. With the aim to determine the level of aerobic endurance. This research is a descriptive study with survey methods and data collection using test and measurement techniques. The population used was all participants of the Men’s Volleyball Student Activity Unit Doktor Nugroho University Magetan totaling 23 students and the samples taken from purposive sampling were 18 students. Aerobic endurance data was taken by measuring the multistage fitness test. The data analysis technique used quantitative descriptive analysis with percentages. There are 33.3% good criteria, 55.5% enough and 11% less. So the analysis of the largest number of levels of Maximum Oxygen Volume (VO2Max) in the Men’s Volleyball Student Activity Unit Doktor Nugroho University Magetan is a sufficient criterion with a figure of 55.5%.